The conundrum of coalition politics in Turkey. (2nd January 2016) - Kalaycioğlu, Ersin
ABSTRACT: Turkey has had a long track record of coalition governments, yet when the June 7, 2015 general elections produced a hung parliament attempts at establishing a new coalition government failed. Why was this so? This paper argues that the non-compromising attitude of the AKP and the MHP, on the one hand, and, on the other hand, the recalcitrance of the President, who perceived any government he had no firm control over as a threat to his political career, undermined any effort at establishing a coalition government. The terror campaign of the PKK and efforts by the AKP and the MHP to demonize the HDP as the party of terror also undermined the chances of the CHP to form a coalition that included the HDP. Hence, Turkey's chances of establishing a democratic government through compromise failed and the country went back to polarizing politics of competitive authoritarianism under the hegemony of the one-party government of the AKP.